Giardiasis in daycare centers at Rancabali tea plantation, Bandung District, Indonesia - Widajanti, Endang; Garna, Herry; Chairulfatah, Alex; Hudaya, Dadang (Paediatrica Indonesiana, 2016)
Background In developing countries, the prevalence of giardia- sis in daycare centers is considerably high. There had been inad- equate report of giardiasis in Indonesia. Objective To know the prevalence of giardiasis in children and the number of children with symptomatic and asymptomatic giar- diasis who attended daycare centers at Rancabali tea plantation, Bandung district. Methods This descriptive study was conducted in daycare cen- ters between August to October 2002. Giardiasis was defined as the occurrence of G. lamblia cyst in stool specimen independent from the presence or absence of symptoms. Four of 12 daycare centers were chosen by cluster random sampling. All children aged 1 to 60 months attending daycare and staying for at least 2 weeks were included in this study. Three consecutive stool specimen pre- served by 10% formalin, concentrated by formalin ether, were ex- amined microscopically to find the G. lamblia cyst. Results Giardia lamblia cysts were found in 27 (29%) of the 92 children attending the daycare centers at Rancabali tea plantation (95%CI 20;38.6%). Of these children, 15 showed symptoms such as diarrhea episodes (8 children), diarrhea (5 children), bloating (5 children), abdominal cramp (5 children), and vomiting (3 children). Three children showed mild to moderate malnutrition. Ten children aged 13 to 36 month-old with G. lamblia-positive stool showed such symptoms. Conclusion The prevalence of G. lamblia infection in children at- tending daycare centers at Rancabali tea plantation was almost similar with other place in developing countries. More than half of patients had symptomatic disease